Some Universal Constructions For I- Fuzzy Topological Spaces (JOURNAL OF ADVANCES IN MATHEMATICS, 2014)
Geetha S. [J. Math. Anal. Appl. 174 (1993), 147-152] has introduced the concept of I-fuzzy topological spaces  X,mu,F)where X is an ordinary set, mu is a fuzzy set in X and F is a family of fuzzy sets in X satisfying some axioms. In this paper we introduce universal constructions, namely, fuzzy products, fuzzy equalizers and fuzzy pullbacks for I-fuzzy topological spaces. Also we discuss some results concerning all such universal objects.